The immune responses to different Uropathogens call individual interventions for bladder infection - Li, Linlong; Li, Yangyang; Yang, Jiali; Xie, Xiang; Chen, Huan (Frontiers in Immunology, 2022)
Urinary tract infection (UTI) caused by uropathogens is the most common infectious disease and significantly affects all aspects of the quality of life of the patients. However, uropathogens are increasingly becoming antibiotic-resistant, which threatens the only effective treatment option available-antibiotic, resulting in higher medical costs, prolonged hospital stays, and increased mortality. Currently, people are turning their attention to the immune responses, hoping to find effective immunotherapeutic interventions which can be alternatives to the overuse of antibiotic drugs. Bladder infections are caused by the main nine uropathogens and the bladder executes different immune responses depending on the type of uropathogens. It is essential to understand the immune responses to diverse uropathogens in bladder infection for guiding the design and development of immunotherapeutic interventions. This review firstly sorts out and comparatively analyzes the immune responses to the main nine uropathogens in bladder infection, and summarizes their similarities and differences. Based on these immune responses, we innovatively propose that different microbial bladder infections should adopt corresponding immunomodulatory interventions, and the same immunomodulatory intervention can also be applied to diverse microbial infections if they share the same effective therapeutic targets.